Flood Hazard Prediction and Land Cover Change Analysis in Tegal Regency for 2045: A Geospatial Approach Using Geographic Information System - Fitrotunnisa, Maulidia Firda; Wibowo, Afif Ari; Surachman, Dedi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this research is to analyze the prediction of flood hazard in 2045 from the flood hazard map and compare it with the 2023 data geospatially using Geographic Information Systems. Methodology: The purpose of this research is to analyze the prediction of flood hazard in 2045 from the flood hazard map and compare it with the 2023 data geospatially using Geographic Information Systems. Results: The results showed that Tegal's highly flood-prone areas would increase by 1.7% in 2045, decreased by 0.59% in prone areas, and decreased by 0.77% in moderately prone areas by 2023. Applications/Originality/Value: One of the causes was a very high land cover change caused by an increase in built-up land and a decrease in vegetation.